Activation of cognitive activity of students techno-pedagogical faculty of design tools (Pedagogy of Higher and Secondary Education, 2012)
Kucher Z. Activation of cognitive activity of students techno-pedagogical faculty of design tools.The article revealed feature senhance the cognitive activity of students with academic planning. Particular attention is paid to the structural components of the projects and the justification of pedagogical conditions of educational design.
Keywords: cognitive activity; project; schoolproject; teaching conditions; principles of design